Detection and destruction of HER2‐positive cancer cells by Ultra Quenchbody‐siRNA complex. Issue 5 (17th February 2020) - Dong, Jinhua; Oka, Yuya; Jeong, Hee‐Jin; Ohmuro‐Matsuyama, Yuki; Ueda, Hiroshi
Abstract: Ultra Quenchbody (UQ‐body) is a biosensor that utilizes the quenching behavior of the fluorescent dye linked to the antibody V region. When the corresponding antigen is bound to the UQ‐body, the fluorescence is restored and allows the detection of target molecules easily and sensitively. In this paper, we constructed UQ‐bodies to sensitively detect the human epidermal growth factor receptor 2 (HER2) cancer marker in solution or on cancer cells, which was further used to kill the cancer cells. A synthetic Fab fragment of anti‐HER2 antibody Fab37 with many Trp residues at hypervariable region was prepared and labeled with fluorescent dyes to obtain the UQ‐bodies. The UQ‐body could detect HER2 in solution at concentrations as low as 20 pM with an EC50 of 0.3 nM with a fourfold response. Fluorescence imaging of HER2‐positive cells was successfully performed without any washing steps. To deliver small interfering RNA (siRNA) to cancer cells, a modified UQ‐body with C‐terminal 9R sequence was also prepared. HER2‐positive cancer cells were effectively killed by polo‐like kinase 1 siRNA intracellularly delivered by the UQ‐body‐9R. The novel approach employing siRNA‐empowered UQ‐body could detect and image the HER2 antigen easily and sensitively, and effectively kill the HER2‐positive cancer cells. Abstract : Rapid and sensitive detection of HER2‐positive cancer cells during diagnosis and/or surgery has been difficult because of the lack of suitable detection reagent. Here, the authors in Tokyo Tech have developed a fluorescent biosensor Ultra Q‐body (UQ‐body) that specifically binds HER2 protein and emits fluorescence. In addition, by fusing 9xArg sequence to the UQ‐body, siRNA for polo‐like kinase was successfully delivered in and killed the cells, showing its potential as a powerful cancer theranostics reagent.